Kegunaan Sistem Informasi Kementrian Sekretariat Negara - Fikri Pramudya; Julian Rafdi; Sulistia Sulistia; Widia Nurhasan; Wijoyo Hartono (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2022)
One area where improvement cannot be halted is technology. Every new technology has the potential to alter how businesses operate and how people live. Utilizing technology is essential for a business to endure and prosper. A management information system has a significant influence and is crucial to management when it is utilized to operate a ministry or agency. Basically, the development inside the Ministry of State Secretariat becomes heavily dependent on the information system. As a result, the goal of this study is to evaluate the information system's use inside the ministry of state secretariat. Researchers' strategy involves speaking with employees of the Ministry of State Secretariat. The findings demonstrate that the Ministry of State's information systems' usefulness has an effect on how well the government performs. The ministry of state secretariat uses hardware, including servers, storage, switches, routers, access points, and virus detection systems, as well as software that is centered on the website, www.sektneg.go.id, to secure data. Systems for managing information play a part in making it simple to take the right action.